SWOT Analysis of Perennial vs Annual Energy Crops: A Case Study in Greece - Annoula Paschalidou; Michael Tsatiris (New Approaches in Engineering Research Vol. 3, 2021)
The EU bio-based economy needs sustainable biomass supply for multiple uses: pharmaceuticals, food, feed, bio-based materials and bioenergy. The yielding potential of the energy crops (annual and perennial) has to be as efficient as possible in order to minimize the competition for land. For the last two decades several perennial and annual energy crops have been cultivated for biofuel production at a European level. The main advantage of the annual energy crops is that agronomic management can be easily adapted from more traditional cultivation practices since they can easily fit in current (rotation) farming systems. On the other hand, perennial energy crops are being specifically developed for biomass production. This paper aims to discuss the most socio-economical and environmentally suited crops for biofuel production in Greece and the Mediterranean area, by comparing some annual and perennial energy crops, through the SWOT Analysis. Our study focuses a) on three perennial energy crops: Miscanthus (Miscanthus giganteus), Cardoon (Cynara cardunculus), and Switchgrass (Panicum virgatum) and b) on four annual energy crops: Sunflower (Helianthus spp.), Kenaf (Hibiscus cannabinus L.), Rapeseed (Brassica napus), Sorghum (Sorghum bicolor). The SWOT results show that the three perennial energy crops under study are an excellent alternative choice for marginal lands, especially since there is no need for annual installation. They have high biomass yields with generally low crop costs (cardoon, switchgrass) and a wide array of end uses. They are particularly beneficial to the environment because they have low chemical requirements (cardoon), high energy content and can be used for soil remediation (miscanthus) and phytoextraction of harmful or polluting substances. However, some have a high initial installation cost, (miscanthus, switchgrass) and some are potentially invasive species (miscanthus, cardoon) while almost all mature crops are particularly flammable. On the other hand the four annual energy crops are some popular and well accepted plants (sunflower, rapeseed) as well some not so widespread ones (kenaf, sorghum as an energy crop). They can be included in the existing rotation farming schemes and most of them can be cultivated with techniques which are already familiar to farmers, similar to the winter cereals (rapeseed). They present an environmentally friendly alternative crop choice, in lands with poor or moderate water availability (sunflower, kenaf), with high yields and a multitude of possible uses, suitable both for small farmers’ cooperatives as well as large scale farming. Choosing the ideal energy crop, annual or perennial, will depend on multiple factors, both socio-economic and environmental.